Altered short-term visual paired associative plasticity in migraine patients between attacks. Issue 1 (January 2019) - Abagnale, C.; Ranieri, F.; Centurioni, C.; Musumeci, G.; Capone, F.; Di Pino, G.; Parisi, V.; Di Lazzaro, V.; Pierelli, F.; Coppola, G.
Abstract : In healthy volunteers (HVs), we recently observed that the rules of the time-dependent paired-associative plasticity found in the sensorimotor system are valid also for the visual system. With the latter method, here, we have tested whether dysfunctioning associative plasticity might characterize the visual system in patients with episodic migraine without aura (MO), where abnormalities in both inhibitory and excitatory paired-associative sensorimotor plasticity have been observed between attacks (1). In 11 MO between attacks and in 14 HVs, we performed a visual paired associative stimulation (vPAS) protocol by coupling 90 black-and-white checkerboard reversals with low-frequency TMS pulses over the occipital cortex at 2 interstimulus intervals in separate sessions by subtracting or adding 25 ms to the visual evoked potential (VEP) P100 latency. We recorded VEPs (600 sweeps) before, after, and 10-min later each vPAS session. VEPs were partitioned in 6 blocks of 100 sweeps. We analysed VEP N1-P1 first block amplitude and delayed habituation. While vPAS-25 significantly enhanced and vPAS + 25 reduced VEP amplitude habituation in HVs, they both did not significantly change VEP amplitude habituation in MO between attacks. We provide evidence for lack of excitability depressing and enhancing short-term associative plasticity mechanisms within the visual system in interictal migraine.